Solar hydrogen generation from organic substance using earth abundant CuS–NiO heterojunction semiconductor photocatalyst - Sudhagar Pitchaimuthu (Ceramics International, 2021)
This work explores the critical role of NiO co-catalyst assembled on the surface of a CuS primary photocatalyst which effectively improves interface properties and enhances solar-to-hydrogen production by prolonging lifetime of photo-excitons generated at the CuS surface. The nanoscale CuS/NiO heterojunction is formulated using hydrothermal and wet impregnation methods. The resultant CuS/NiO composite shows optical absorbance between 380-780 nm region. The type-II energetic structure formed at CuS/NiO heterojunction facilitates rapid charge separation and as a result, the CuS/NiO composite exhibits 13 folds higher photocatalytic water splitting performance than CuO and NiO. The champion CuO/NiO photocatalyst is first identified by screening the catalysts using a preliminary water splitting test reaction under natural Sunlight irradiation. After the optimization of the catalyst, it was further explored for enhanced photocatalytic hydrogen production using different organic substances dispersed in water (alcohols, amine and organic acids). The champion CuS/NiO catalyst(CPN-2) exhibited the photocatalytic hydrogen production rate of 52.3 mmol.h-1.g-1cat in the presence of lactic acid-based aqueous electrolyte and, it is superior than hydrogen production rate obtained in the presence of other organic substances (triethanolamine, glycerol, ethylene glycol, methanol) tested under identical experimental conditions. These results indicate that the energetic structure of CuS/NiO photocatalyst is favorable for photocatalytic oxidation of lactic acid or reformation of lactic acid. The oxidation of lactic acid contributes oxidative electrons for enhanced hydrogen generation as well as protects CuS from photocorrosion. The modification of surface property and energetic structure of CuS photocatalyst by the NiO co-catalyst improves photogenerated charge carrier separation and in turn enhances the solar-to-hydrogen generation. The recyclability tests showed the potential of CPN-2 photocatalystfor prolonged photocatalytic hydrogen production while continuous supply of lactic acid feedstock is available.